The development of depression and social anxiety symptoms in adolescents and the negative impact of the COVID-19 pandemic and desire for peer contact - Pinkse-Schepers, Anne L.; Buil, J. Marieke; Sijtsma, Hester; Hollarek, Miriam; Walsh, Reubs J.; van Buuren, Mariët; Krabbendam, Lydia; Lee, Nikki C. (Frontiers in Public Health, 2024)
Introduction: Adolescence is a dynamic developmental phase in which contact with peers is crucial for socio-emotional development and wellbeing. Depression and social anxiety show patterns of high onset during this period, and more for girls than boys. Here we examine this development among Dutch adolescents, as well as how desire for more peer contact as a result of social distancing measures during the COVID-19 pandemic contributed to this increase.: We used a longitudinal three-wave design to examine 406 typically developing Dutch adolescents across two consecutive cohorts; Cohort 1: 2016-2019 (N=138, 53.6% girls, age at T0 M = 13.00, SD = 0.42), Cohort 2: 2017-2020 (N=268, 63.1% girls, age at T0 M = 13.05, SD = 0.39), final wave during spring 2020 during the first COVID-19 lockdown. Selfreport questionnaires were used to measure depression and social anxiety symptoms, desire for change in the amount of peer contact during lockdowns, and emotion regulation . Parallel process dual latent growth models and autoregressive cross-lagged models were used to test the hypotheses.Results: Results showed that symptoms of both depression and social anxiety increase during adolescence. Gender analysis reveal a higher initial level and increase in depression symptoms for girls, while levels for boys decreased. Adolescents exposed to the pandemic showed a steeper increase in depression but not in social anxiety. Desire for more peer contact was related to an increase in depression and social anxiety, though only in girls. No evidence was found for moderation of emotion regulation skills concerning COVID evoked emotions on the association between desire for peer contact and anxiety and depression symptom development.Discussion: Symptoms of social anxiety increased during adolescence in boys and girls.Symptoms of depression increased for girls as well, but decrease for boys. The increase in depression was greater in a cohort who experienced the COVID-19 pandemic. For girls, a desire for more peer contact was associated with an increase of depression and social anxiety symptoms in times of social restrictions.